REPRESENTATION OF NONVERBAL ASPECTS OF THE CHARACTERS CREATED BY A.AKHMATOVA AND M. TSVETAEVA - Yovkacheva Z. М (Galaxy International Interdisciplinary Research Journal, 2021)
The linguistic science of recent decades is characterized by switching the attention of scientists with structural-semantic problems to functional-communicative, and in connection with the object of research increasingly becomes the phenomenon of a linguistic personality, which can be studied in various aspects: properly linguistic, psychological, cultural, etc. Currently, work on the study of genre originality is not only the cycles of A. Akhmatova, but also separate poems. The genre, style, thematic, meaningful, rhythmic diversity of the creative heritage M. Tsvetaeva led to the formation of several directions of modern coloring.